Physiologic risk factors for early acute kidney injury in severely injured patients - Sklienka, Peter; Máca, Jan; Neiser, Jan; Burša, Filip; Ševčík, Pavel; Frelich, Michal; Patejová, N; Švagera, Zdeněk; Tomášková, Hana; Záhorec, Roman (Bratislavské lekárske listy, 2020)
BACKGROUND: The evaluation of the predictive value of the neutrophil gelatinase-associated lipocalin (NGAL) for an early acute kidney injury (AKI) development in severely injured patients. Determination of the time-dependent roles of trauma-related physiologic markers of tissue hypoxia, systemic inflammation and rhabdomyolysis in AKI development. METHODS: 81 adult patients were screened for the presence of AKI for eight consecutive days following the injury. Arterial levels of plasma NGAL, lactate, interleukin-6, procalcitonin, and myoglobin were investigated at 24 hours (T1), 48 hours (T2), and 96 hours (T3) after the injury. RESULTS: The incidence of AKI was 32.1 %. Patients with AKI were older, but no significant difference in injury severity was observed. NGAL levels were significantly higher in the AKI group at T1, T2, and T3 when compared to the non-AKI group. Lactate levels were significantly higher in the AKI group at T2 only, and IL-6 levels were significantly higher in the AKI group at T2 and T3. Procalcitonin and myoglobin levels were significantly higher in the AKI group at T1, T2, and T3, when compared to the non-AKI group. Positive correlations were found between plasma NGAL and all screened physiological factors at all defined time points. CONCLUSION: Development of AKI after blunt trauma is very complex and multifactorial. Activation of the systemic inflammatory response and rhabdomyolysis (high concentration of myoglobin) were strongly involved in AKI development. Blood NGAL levels after injury were significantly higher in patients, who developed posttraumatic AKI. Plasma NGAL, lactate, procalcitonin, interleukin-6, and myoglobin had potential to be useful parameters for risk stratification and prediction of AKI after trauma (Tab. 6, Ref. 40).
Keywords: Rhabdomyolysis; dospělí; lipokalin-2; Statistics as Topic; zánět; Hypoxia; statistika jako téma; akutní poškození ledvin; Adult; lidé; Wounds and Injuries; Inflammation; hypoxie; Risk Factors; Lipocalin-2; rhabdomyolýza; rizikové faktory; rány a poranění; Acute Kidney Injury; Humans